THE PROPERTIES OF THE MATERIAL GADOLINIUM AND THE WORKING AGENT USED IN THE INSTALLATION OF MAGNETIC REFRIGERATION DEVICES - Dorin , Botoc; Avsec, Jurij; Plesca, Adrian; Georgel, Gabor; Ionut, Rusu (Journal of Energy Technology, 2024)
Much remains to be done to understand better and thus achieve better control over magnetic materials to maximize their magnetocaloric properties and performance, specifically for gadolinium. A clear path forward is highlighted by thorough experiments coupled with theory, in which the latter is tested and refined against the former, thus resulting in discoveries of new and improved materials and bringing near-room-temperature magnetic refrigeration technology to fruition in the near future.